Ground Control Aspects of Mining Deep Remnant Panels at Falconbridge Lockerby Mine ? A Case Study - J. Ran (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
There are challenges in mining deep tabular ore deposits using the open stoping method, particularly mining remnant panels towards the end of mine life. The remnant panels have experienced stress concentration and are in the failing or post failure state causing drilling and loading difficulties, ground movement, induced seismicity and ground instability problems. As more mines are going deep, without effective ground control management, the mine production will be interrupted and equipment damage and personnel injury are likely to occur. Mining at Falconbridge Lockerby Mine located in the Sudbury Basin was concentrated in the deep zone from late 1990s to 2004. The remnant panels situated approximately from 1800m to 1920m below surface were mined in 2004 before the mine closure. These panels were in the central section of the orebody along strike. The orebody was relatively narrow ranging from 5m to 15m and steep dipping at 70o to 80o. Because of the retreat mining sequence and the mining depth, stress concentration, wall closure and seismicity had caused a number of mining difficulties. Managing these challenges was critical in achieving the mine production target without compromising personnel safety and excavation stability. A comprehensive ground control management approach was adopted to mine the remnant panels at depth. The measures taken included ground movement monitoring, understanding the movement pattern of the footwall rock and selecting appropriate support systems, analyzing seismic monitoring data and defining re-entry protocol, brow support design and restricting access. This paper presents these ground control measures and the experience gained in successfully mining the deep remnant panels at Lockerby Mine.